Epigenetic regulation of the histone-to-protamine transition during spermiogenesis. Issue 5 (May 2016) - Bao, Jianqiang; Bedford, Mark T
Abstract: In mammals, male germ cells differentiate from haploid round spermatids to flagella-containing motile sperm in a process called spermiogenesis. This process is distinct from somatic cell differentiation in that the majority of the core histones are replaced sequentially, first by transition proteins and then by protamines, facilitating chromatin hyper-compaction. This histone-to-protamine transition process represents an excellent model for the investigation of how epigenetic regulators interact with each other to remodel chromatin architecture. Although early work in the field highlighted the critical roles of testis-specific transcription factors in controlling the haploid-specific developmental program, recent studies underscore the essential functions of epigenetic players involved in the dramatic genome remodeling that takes place during wholesale histone replacement. In this review, we discuss recent advances in our understanding of how epigenetic players, such as histone variants and histone writers/readers/erasers, rewire the haploid spermatid genome to facilitate histone substitution by protamines in mammals.